﻿Measurement of air temperature using laser interferometry - Ali , ﻿Ahmad Hadi (2010)

(untitled)
﻿Abstract-Measurement of gas temperature is very crucial in laser induced plasma (LIP) and laser material interaction (LMI). Temperature monitoring devices such as thermocouple has some limitations. The thermocouple can not be placed at the laser focusing region since it will induce unwanted external effect. To overcome, a non-contact method is proposed by using interferometric technique. A simple Michelson interferometric was aligned to detect the pressure and refractive index change of ambient air. The temperature gradient of air were recorded and analyzed by using a video camera and phototransistors.From the observation results, it clearly shown that the change of air temperature in one arm of the interferometer will result in the fringes shift of the interference pattern.